SPE Gas Technology Symposium 2002
DOI: 10.2118/75717-ms
|View full text |Cite
|
Sign up to set email alerts
|

Permeability, Pore Pressure, and Leakoff-Type Distributions in Rocky Mountain Basins

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe permeability, pore pressure, and leakoff-type interpreted from more than 1,200 diagnostic fracture-injection/falloff tests were collected in a database and statistically evaluated for four Rocky Mountain basins. The statistical analysis includes the range of observed permeability and pore pressure and the fracture leakoff-type distribution.Specially designed "mini-frac" or diagnostic fractureinjection/falloff tests were routinely implemented throughout Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…810 tests showed that 61% of the tests had pressuredependent leakoff, indicating the presence of natural fractures (Craig et al, 2005). Additional evidence of abundant natural fractures is provided by numerous image logs that have been obtained in the Piceance Basin in recent years (Koepsell et al, 2003).…”
Section: Geologic Settingmentioning
confidence: 94%
“…810 tests showed that 61% of the tests had pressuredependent leakoff, indicating the presence of natural fractures (Craig et al, 2005). Additional evidence of abundant natural fractures is provided by numerous image logs that have been obtained in the Piceance Basin in recent years (Koepsell et al, 2003).…”
Section: Geologic Settingmentioning
confidence: 94%
“…As a result many potential solutions have been attempted in the past including pure oil fracs, CO2 energized oil fracs, cross-linked water based fracs, poly-emulsion fracs and water based foam fracs. 27 More than 1,200 diagnostic fracture injection tests (DFIT) performed in the U.S. Rocky Mountain Area between 1998 and 2001 were evaluated consistently by Craig et al 28 for estimating permeability, pore pressure and leakoff type. Permeabilities ranged from less than 0.001 to more than 0.1 md.…”
Section: Drilling Completion and Stimulationmentioning
confidence: 99%